Mapping large bodies of research in environmental sciences: insights from compiling evidence on the recovery and reuse of nutrients found in human excreta and domestic wastewater - Robin Harder (Environmental Evidence)
Abstract Mapping evidence on a particular research topic among others aims to provide a comprehensive overview of the topic along with a searchable database of relevant literature. When attempting to map large bodies of research, mappers may soon find themselves in a situation where the resources available for the mapping are incommensurate to the number of studies to be handled. This typically requires either a narrower scope of the map or a streamlined mapping process. Grounded in a comparison of five evidence maps on the topic of recovery and reuse of nutrients found in human excreta and domestic wastewater—some of them systematic, some not—the present paper sets out to quantify the potential effect of procedural differences on mapping outcomes. Ultimately, the goal is to discern the factors that matter most for comprehensive and balanced mapping outcomes. This exploration suggests that a good search strategy is key when mapping large bodies of research, especially so when terminology is barely standardized. The paper also sheds light to an issue that could be described as differential search term sensitivity and specificity (compound search terms that are not equally sensitive and specific across all subdomains of the map) and that may deserve more attention in evidence mapping. Drawing from my experiences from compiling the online evidence platform Egestabase, the paper sketches how this issue might be mitigated. In addition, the paper outlines several measures that can help achieve substantial efficiency gains, and offers reflections on how to set priorities and navigate tradeoffs when a standard systematic mapping process appears not to be viable and not strictly necessary.